Fusion Prostate Biopsy Outperforms 12-core Systematic Prostate Biopsy in Patients with Prior Negative Systematic Biopsy: A Multi-Institutional Analysis - Sidana, Abhinav (Urol Oncol, 2018)
INTRODUCTION AND OBJECTIVES: Patients with persistently elevated prostate specific antigen (PSA) and prior negative 12-core TRUS prostate biopsy (or biopsies) (SBx) are a diagnostic challenge. Repeat SBx or saturation biopsy in this cohort has been shown to have an even lower yield. The aim of our study is to compare the prostate cancer yield of MRI fusion biopsy (FBx) to SBx in a multi-institutional cohort comprised of patients with prior negative biopsies. METHODS: A multi-institutional review was performed on patients with a history of one or more prior negative SBx who underwent multiparametric MRI (MpMRI), followed by FBx and SBx in the same session. Imaging protocol was standardized across institutions and institutional genitourinary radiologists and pathologists reviewed mpMRI and pathology, respectively. Gleason Score (GS) distribution and risk classifications were recorded. Prostate cancer with GS ≥ 3+4 was defined as clinically significant (CS). Univariate and multivariable logistic regression was done to identify predictors of cancer detection on SBx and FBx. RESULTS: Seven-hundred seventy-nine patients from four institutions were included in the study. Median age and PSA (IQR) were 63.1 (58.5-68.0) years and 8.5 (5.9-13.1) ng/dL, respectively. Median number of prior negative biopsies (range) was 2.0 (1-16). The cancer detection rate (CDR) in the cohort was 346/779 patients (44.4%). Total CS CDR was 30.7% (239/779 patients), with FBx detecting 26.3% (205/779) of patients with CS disease and SBx diagnosing an additional 4.4% (34/779) of patients (p<0.001). Furthermore, of all cancers detected by each modality, FBx detected a higher proportion of CS cancer compared to SBx (One negative biopsy: 75 versus 50%, p<0.001, 2-3 negative biopsy: 76 versus 61%, p =0.006, 4 or more negative biopsies: 84 versus 52%, p=0.006). As such, SBx added a relatively small diagnostic value to FBx for detecting CS disease (One negative biopsy 3.5%, 2-3 negative biopsies 5%, 4 or more negative biopsies: 1%). FBx also outperformed SBx for upgrading patients to an intermediate or high-risk cancer category (GS >6) (One negative biopsy 11.5% versus 3.6%, 2-3 negative biopsy 10.3% versus 5.3%, 4 or more negative biopsies 19.1% versus 1.1%). On multivariable analysis, the number of prior negative biopsies was a significant negative predictor of CS CDR on SBx (p=0.006), but not on FBx (p=0.151). CONCLUSIONS: Using a large multi-institutional cohort, we were able to demonstrate that FBx outperformed SBx in patients with prior negative systematic biopsy. This was due, in part, to the decreasing CS CDR by SBx with increased number of prior biopsies. The yield of FBx stayed constant and did not decrease with increased number of prior negative biopsies. Therefore, repeat SBx alone in patients with multiple prior negative biopsies will be hindered by lower yield and FBx should be utilized concurrently in these patients.